Detection of muscular system adverse reaction signals in sacubitril/valsartan treatment combined with statins - Zhao, Fukun; Luo, Min; Wang, Yuanmin; Su, Mu; Tang, Fei (Frontiers in Pharmacology, 2024)
Objective: To detect muscular system adverse reaction signals of sacubitril/valsartan treatment combined with statins (atorvastatin, rosuvastatin, simvastatin) to provide a reference for clinical administration. Methods: Multiplicative and additive models were used to mine the FDA's spontaneous reports database to detect signals of drug-drug interactions between sacubitril/valsartan and statins. SAS 9.4 software was used to conduct statistical tests for suspicious signals to determine whether the signals were statistically significant. Results: A total of 8,883,870 adverse reaction reports were analyzed. The combinations "sacubitril/valsartan - simvastatin - musculoskeletal muscle pain" had statistically significant correlation signals in both models (P<0.05). The combination "sacubitril/valsartan - atorvastatin - myopathy" and "sacubitril/valsartan – simvastatin - myopathy" had statistically significant correlation signal in the multiplicative model (P<0.05). Conclusions: Compared with a single drug, coadministration of sacubitril/valsartan with atorvastatin may increase safety risks to myopathy, with simvastatin may increase safety risks to the musculoskeletal pain and myopathy, which should be closely monitored in clinical practice.